33rd AIAA Applied Aerodynamics Conference 2015
DOI: 10.2514/6.2015-3151
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a Flapping Wing UAV using a Coupled CFD-Control Tool

Abstract: A tool is developed to couple high-fidelity CFD computations with a vehicle feedback controller. Using a flapping-wing geometry as a vehicle test case, wing stroke kinematics are extracted from experimental trials and simulated in a computational environment to determine wing force time histories. The pitch dynamics of the vehicle are studied and a closed-loop controller is implemented to effect changes in vehicle pitch attitude through biasing the wing stroke midpoint. Simulations show successful implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It can be found that the wing was excited at 14 Hz, with negative drag indicated as positive thrust with high Cl . Geder et al [ 48 ] used FEFLO software to perform CFD simulation on a flapping wing geometry inspired by a bird. The authors studied wing kinematics, aerodynamic forces, and pitch altitude control on the model of a flapping wing, in which both kinematics and flow environment affected the wing forces and captured the flow physics by using a reduced-order model.…”
Section: Research On Biomimetics Related To Cfd Applicationsmentioning
confidence: 99%
“…It can be found that the wing was excited at 14 Hz, with negative drag indicated as positive thrust with high Cl . Geder et al [ 48 ] used FEFLO software to perform CFD simulation on a flapping wing geometry inspired by a bird. The authors studied wing kinematics, aerodynamic forces, and pitch altitude control on the model of a flapping wing, in which both kinematics and flow environment affected the wing forces and captured the flow physics by using a reduced-order model.…”
Section: Research On Biomimetics Related To Cfd Applicationsmentioning
confidence: 99%